Capacitors with sand-particle interlayer. (25th August 2022) - Duan, Li; Han, Kui; XIE, Li
Abstract: Sand is common in desert and beach, with few other large-scale applications in history except for construction. The electricity storage phenomenon of sand particles is discovered, and for the first time the Sand Interlayer Capacitor (SIC) is developed with graphite paper electrodes and sand-particle interlayer. The SIC devices exhibit the best electrochemical performance in comparative experiments. Its specific capacitance per unit area can reach up to 24.68mF/cm 2, as high as 1000 times that of capacitors with pure graphite electrodes, being compared with some of activated carbon capacitors and nano‑carbon capacitors, etc. In addition, the SIC shows excellent cycling durability. Under 5000 charge-discharge cycles, the coulombic efficiency and capacitance retention rate are both stable around 100 %. For 30-day continuous operation, the specific areal capacitance of the SIC can still be stable at around 28mF/cm 2 . The SIC is promising to be used in desert energy storage systems. Highlights: The Sand Interlayer Capacitor is a brand-new capacitor with sand-particle interlayer with a novel method of fabrication. The Sand Interlayer Capacitors show good electrochemical performance. The Sand Interlayer Capacitors show the possible application in desert energy-storage systems.